La crisi della cultura europea nelle opere dei filosofi russi del Novecento: a proposito delle idee di Oswald Spengler - Belov, Vladimir N. (Filosofia, 2015)
The present paper explores the positions of four Russian intellectuals on the work of Oswald Spengler. Fëdor Stepun maintains that, despite the dubious originality of his conception, Spengler distinguishes himself for the depth of his reflections on the concept of death, which in his opinion might rekindle religious life. Nikolaj Berdjaev believes that the German thinker succeeds in compensating for the lack of a religious dimension thanks to an in-depth, though somewhat am- biguous, reflection on technique, above all with specific reference to the Russian world. Semën Frank critiques Spengler’s pessimism, out of the belief that moments of crisis unlock further historical development. Matvej Kagan compares and con- trasts Natorp’s position, which is based on infinite variables and is open to the future, with Spengler’s ideas, which are centered on finite structures and look back to the past. The comparison undertaken by the aforementioned authors with Spen- gler’s work has been a major source of progress for Russian philosophical thought, with a view to an ideal harmonization with the European spirit.